Continuous passive motion (CPM): Characteristics of application and case reports [SUREKLI PASIF HAREKET (SPH): UYGULAMA OZELLIKLERI VE OLGU SUNUMLARI] - (:unkn) unknown (My University, 1995)
Continuous passive motion (CPM) is a technique of rehabilitation that involves passive movement of an extremity through an externally applied force. Animal studies have revealed that CPM increases the healing of the articular cartilage, prevents focal articular degeneration, degenerative arthritis and intraarticular adhesions and effusion. CPM is recently being used widely in the early postoperative period of various joint surgical procedures, as studies have suggested its value. Besides preventing joint contractures, CPM can also be applied in the management of joints with established contractures. In this paper 2 cases with postoperative knee contractures were presented and the beneficial effects with CPM application were reported.
Keywords: Joint; Passive motion; Rehabilitation